Acute Adrenal Hemorrhage as the Initial Manifestation of Metastatic Lung Adenocarcinoma: A Cautionary Tale - Sowbharnika Arivazhagan; Guru Prasad Parthiban; Christina Patterson; Karthik Reddy (Case Reports in Oncological Medicine)
Adrenal gland metastatic disease is the most commonly occurring malignancy of the adrenal glands. Although metastatic disease is common, adrenal hemorrhage is a rare but potentially fatal manifestation of malignancy. The objectives of this case report are to highlight the unusual presentation of metastatic lung adenocarcinoma as spontaneous adrenal hemorrhage in a 64-year-old female who was otherwise asymptomatic. As well as to support the reasoning that metastatic disease should be considered as a differential in patients with this clinical presentation as this may have altered this fatal outcome.